Numerical and Experimental Investigations of Cesium and Strontium Sorption and Transport in Agricultural Soils - Berns, A.E. (2020)
We identified undefined cation exchange as the dominant sorption process for Sr2+, followed by surface complexation on organic matter. These process‐based analyses were the basis for field‐scale simulations to predict the leaching risk of Cs and Sr radionuclides in agricultural soils under humid climate conditions. For both soils and radionuclides, the distribution coefficients (Kd) varied distinctly with time in shallow layers due to changes in temperature, saturation, and the prevailing dominant sorption processes. During a 3‐yr‐simulation period, 137Cs+ migrated to depths of 3.6 cm (silty loam) and 7.6 cm (sandy loam), while 90Sr2+ migrated to depths of 15.6 cm (silty loam) and 23.6 cm (sandy loam) due to competitive sorption of infiltrating Ca2+ and Mg2+ ions reducing 90Sr2+ sorption and displacing 90Sr2+ from its exchange sites.